BENARKAH SELF ESTEEM MEMPENGARUHI PRESTASI AKADEMIK? - Wibowo, Satrio Budi (HUMANITAS, 2016)
AbstractSelf-esteem determines a person’s overall mental development, it can even affect human behavior. The debate arose when researchers try to explain, whether student achievement is influenced by self-esteem? The author conducted a meta-analysis studies in attempt to clarify the relationship between the variables of self-esteem with academic achievement variable. This research analyzed over sixteen research journals, in which there are 29 studies that examine a relationship between self-esteem and academic achievement. Fifteen research journal use Global Self-esteem scale of the artificial factor in measuring the Rosenberg self-esteem, and research journals using the scale of the Tennessee Self-Concept Scale (TSCS). Academic achievement in 16 research journals obtained, operationalized as the average value of the end of the previous school year students and test scores of students in certain subjects. The analysis showed that there is a significant correlation between self-esteem with academic achievement. The correlation coefficient obtained population is low, amounting to 0,199. The weak correlation coefficient can not be concluded that self-esteem does not affect academic achievement. However, there are two alternatives that could explain the lack of connection between self-esteem with academic achievement. First, the relationship between self-esteem with academic achievement is a two-way relationship. Second, the relationship between self-esteem with academic achievement associated with academic self-efficacy variables.Keywords: academic achievement, self-esteem, the meta-analysis